1976
DOI: 10.1039/dt9760000342
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic anisotropy in cobalt(II) Schiff-base complexes. X-Ray crystal structure and electron spin resonance of NN′-ethylenebis-(acetylacetoneiminato)cobalt(II)-doped NN′-ethylenebis(acetylacetone-iminato)nickel(II)

Abstract: The e m . study of a single crystal of NN'-ethylenebis(acetylacetoneiminato)cobalt(ii)-doped NN'-ethylenebis-(acetylacetoneiminato)nickel(ii), [Co(acacen)] and [Ni(acacen)], is reported ; determination of the ground state of the cobalt complex was attempted. [Ni(acacen)] Is isomorphous with [Co(acacen)] as shown by a single-crystal structural determination : the doped crystals are orthorhombic. space group Pna2,. Z = 4, a = 12.1 8(1), b = 10.28(1), and c = 10.37(1). The equatorial principal axes of the g tenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The orientations of the g and A principal axes system with respect to the molecular frame are consistent with those found in similar compounds [9,28]. Only for Coacacen in anhydrous Niacacen have Cariati et al found that gxx bisects the molecular x,y axes [17]. Daul et al have pointed out, however, that after a detailed reconsideration of these data an assignment of the gxx axis parallel to the twofold molecular axis x is more plausible [9].…”
Section: Comparison With Earlier Epr Studiessupporting
confidence: 60%
See 2 more Smart Citations
“…The orientations of the g and A principal axes system with respect to the molecular frame are consistent with those found in similar compounds [9,28]. Only for Coacacen in anhydrous Niacacen have Cariati et al found that gxx bisects the molecular x,y axes [17]. Daul et al have pointed out, however, that after a detailed reconsideration of these data an assignment of the gxx axis parallel to the twofold molecular axis x is more plausible [9].…”
Section: Comparison With Earlier Epr Studiessupporting
confidence: 60%
“…In the E.P.R./ENDOR measurements two magnetically inequivalent sites were observed for Coacacen in Niacacen'l/2H20 in contrast to the anhydrous form of Niacacen, where four inequivalent sites have been found [17]. The spectra of the two sites of the hemihydrate crystal coincide only for the rotation around axis I (cf.…”
Section: Epr Spectramentioning
confidence: 95%
See 1 more Smart Citation
“…The geometry of the complex has been adopted from X-ray crystallographic data determined by Cariati et al [26]. Since the deviation from C 2v symmetry is not significant we have chosen to impose this symmetry in our calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…To avoid gauge dependence of the g-values upon the origin chosen for the magnetic field if one uses a finite basis set, the gauge including atomic orbitals (GIAO) [42,43] method was used. The experimental geometries based on X-ray crystallographic data determined by Cariati and coworkers [44] were adopted. Calculations were done for four Co(II) complexes that are shown in Fig.…”
Section: Computational Detailsmentioning
confidence: 99%